Data visualization in hybrid space: constraints and opportunities for design - Marques, Ana Beatriz (2024)
It is intended to investigate the hybrid space, as a determining attribute of the experience and interaction with augmented reality systems, to assess the potential and limitations of this space for information design, specifically in the context of data visualization. This paper presents a study which focused on the use of augmented reality in data visualization, in cases where there is no direct semantic relation between the virtual content and the real setting where the visualization will be displayed. For this study, a practice-based methodology was adopted, supported by the development, implementation and testing of a prototype of an augmented reality application for mobile devices. This prototype, which allows to visualize data related to design companies in Portugal, was assessed in real context. The data collected in this process sparked a reflection on the achieved results, but also on the challenges inherent to the application of this technology in the design of data visualizations.